Assessment of the potential impacts of trap usage and ghost fishing on the Northern Demersal Scalefish Fishery - Newman, S.; Skepper, C.; Mitsopoulos, G.; Wakefield, C.; Meeuwig, J.; Harvey, Euan (Taylor & Francis Inc., 2011)
Fish traps are the principal fishing gear used in the Northern Demersal Scalefish Fishery. These fish traps are left at sea (dumped) between trips and are occasionally lost. The present study quantified the number of fish caught by baited fish traps set on the seabed and left to fish over the short (~3 hr, within a trip) to medium term (12 days, between trips). Trapscontinued to retain fish for the duration of the experiment, despite the fact that all bait was exhausted within 3 hr. The catch rate of the traps was not significantly different for a range of teleost species and species groups over the 12-day duration of the experiment, with some exceptions. Catches after the 12-day soak time were similar to those soak times of only a few hours for most species and species groups. Importantly, despite the ability of fish to enter and exit traps, traps set for several days continue to catch fish. Fisheries monitoring and management implications primarily include errors in catch rate estimates from unaccounted fishing effort (soak time) from dumped traps and/or secondarily unaccounted mortality from lost fishing gear, both of which result in increased uncertainty in stock assessments.